Journal of British Studies (JSTOR)
The official publication of the North American Conference on British Studies (NACBS), the Journal of British Studies, has positioned itself as the critical resource for scholars of British culture from the Middle Ages through the present. Drawing on both established and emerging approaches, JBS presents scholarly articles and books reviews from renowned international authors who share their ideas on British society, politics, law, economics, and the arts.
Keywords: British Studies